Extraction, Phytochemistry & Pharmacological Potential of Camellia sinensis: A Comprehensive Review - Kaur, Prabhjot; Gandhi, Simran; Sharma, Rubal; Kaur, Lovepreet; Pal, Mahak; Deswal, Geeta; Chopra, Bhawna; Grewal, Ajmer Singh; Dhingra, Ashwani K. (Natural Products Journal, The, 2024)
Camellia sinensis (L.) is acknowledged globally as the second most consumed beverage after water. Researchers have dedicated substantial efforts to validate the claims surrounding this plant through rigorous pharmacological screening, aiming to substantiate its traditional applications in treating various ailments. This work extensively delves into aspects such as marketed formulations of green tea, extraction techniques, phytochemistry, pharmacology, interactions between drugs and green tea, and its distinctive characteristics. Key research unequivocally suggests that green tea holds substantial health benefits for individuals. Presently, a multitude of pharmacologically active constituents have been successfully isolated and identified from green tea, encompassing polyphenols, alkaloids, amino acids, polysaccharides, and volatile components. Recent investigations have illuminated the broad spectrum of pharmacological properties exhibited by green tea, encompassing antioxidant, anticancer, hypoglycemic, antibacterial, antiviral, and neuroprotective attributes. The review amalgamates current research findings to present a thorough understanding of the diverse bioactive compounds found in Camellia sinensis, such as polyphenols, catechins, and alkaloids, and their contributions to its health-promoting properties. The review further highlights the significance of extraction techniques in preserving and enhancing the bioactivity of these compounds. Overall, this comprehensive review serves as a valuable resource for researchers, practitioners, and enthusiasts, consolidating the current knowledge surrounding Camellia sinensis and its multifaceted role in promoting human health.
Keywords: antioxidant